Data for Studying Earnings, the Distribution of Household Income and Poverty in China - Björn Anders Gustafsson; Shi Li; Hiroshi Sato (Institute for the Study of Labor (IZA), 2014)
This paper discusses data used in publishing statistics on earnings, the distribution of household income and poverty in China by the National Bureau of Statistics (NBS) which is widely used by policy makers, international agencies and researchers. Unlike many other countries, China until recently had a dual system of household surveys - one rural and one urban. This has had consequences for providing official data on wages, income and poverty which we discuss along with other challenges. Since the end of the 1980s, researchers have been active in the construction of large databases aimed at mapping earnings, household income and poverty, and we present seven of these in the paper.
Keywords: C83; D31; I32; P36; 330; earnings; income; inequality; poverty; data; China; National Bureau of Statistics